THE ROLE AND AUTHORITY OF SATPOL PP IN REGULATING STREET VENDORS ACCORDING TO QANUN NO. 3 OF 2007 AND HAQQ AL-MURŪR (A Study in the City of Banda Aceh) - Salsabila; Ali, Bukhari; bin Adnan, Boihaqi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
Legally, Qanun of Banda Aceh City No. 3 of 2007 provides a clear legal foundation for the local government, through the Civil Service Police Unit (Satpol PP), to regulate, guide, and control street vendors (PKL). Satpol PP holds the authority to maintain and uphold public order by the mandate of the qanun. In practice, however, many street vendors in Banda Aceh still operate in areas that disrupt public order, such as sidewalks, parks, and other public spaces. Haqq al-Murūr means right of passage or right to the road, referring to a person's right to use public roads or spaces, such as alleys, streets, or other communal areas. Therefore, this study examines the extent of Satpol PP's role and authority in enforcing order over street vendors in Banda Aceh City. The study uses a descriptive method with an empirical juridical approach to address this issue. The findings conclude that the implementation of Qanun No. 3 of 2007 has generally moved toward achieving public order, but still faces significant challenges in fully embodying the values of Haqq al-Murūr. One of the main issues is that street vendors continue to sell in prohibited areas because they consider the designated relocation sites unstrategic and feel that enforcement is unfair, especially when formal shops are still allowed to use the roadside for commercial purposes. Therefore, public policies should be strengthened to become more people-centered, so that law enforcement is not only legal but also ethical, moral, and beneficial for all parties involved